Understanding the Effects and Adverse Reactions of Deep Brain Stimulation: Is It Time for a Paradigm Shift Toward a Focus on Heterogenous Biophysical Tissue Properties Instead of Electrode Design Only? - Ineichen, Christian; Shepherd, Naomi Ruth; Sürücü, Oǧuzkan (Frontiers in Human Neuroscience, 2018)
Deep brain stimulation (DBS) has been proven to be an effective treatment modality for various late-stage neurological and psychiatric disorders. However, knowledge on the electrical field distribution in the brain tissue is still scarce. Uptodate,Most recent attempts to e perspective of understand ding electric field spread was were primarily focused on the effect of different electrodes on rather simple tissue models. The influence of microanatomic, biophysical tissue properties in particular has not been investigated in depth. Ethical concerns restrict thorough research on field distribution in human in vivo brain tissue. By means of a simplified model, we investigated the electric field distribution in the a vicinitybroader area of the subthalamic nucleus (STN). Pivotal biophysical parameters including conductivity, permittivity and permeability of brain tissue were incorporated toin the model. A brain tissue model was created with using the finite element method (FEM). Stimulation was mimicked with parameters used for for monopolar stimulation of patients suffering from Parkinson’s disease. Our results were visualized with omnidirectional and segmented electrodes. The stimulated electric field was visualized with superimpositions on a stereotactic atlas (Morel). Owing to the effects of regional tissue properties near the stimulating electrode, marked field distortions occur. Such effects include, for example, isolating effects of heavily myelinated neighboring structures, e.g. the internal capsule. In particular, this may be illustrated through the analysis of a larger coronal area. Whileereas omnidirectional stimulation has been associated with a vast current leakage, higher targeting precision could bewas obtained with segmented electrodes. But Finally, targeting was improved optimal increased when the influence of microanatomic structures on the electric spread was considered. Our results demonstrate confirm that lead design is not the sole influence on current spread cannot be foreseen based on lead design only. An omnidirectional lead configuration does not automatically result in an omnidirectional spread of current. Segmented In turn, segmented electrodes do not automatically imply an a truea improved steering of current. Our findings may provide an explanation for side-effects secondary to current leakage. Furthermore, a possible explanation for divergent results in the comparison of the intraoperative awake patient and the postoperative setting is given.